Engaging policy makers: how to make the message pass?. (30th September 2020) - Greco, D
Abstract: Vaccination remains a serious matter of concern from a relevant part of the population, therefore a quite delicate issue for policy-makers. The paradox between vaccination success and vaccination hesitancy is a current issue: the more vaccination has been successful in eliminating or reducing the incidence of diseases the lower the perception of risk among younger parents' cohorts that never saw diseases for which their children are requested to be vaccinated. This hesitancy is reflected in the politicians' space, as they are quite reluctant to impose measures that will target the mass of healthy young children potentially raising negative reaction from the parent's population. Financial issues are not a concern in the rich world: vaccination global budget is a small fraction of the running health expenditures; money is still a problem in developing countries, but there population and politicians do accept happily donation for new vaccination campaigns. But the situation is quickly changing: in the northern hemisphere, despite the growth of vaccination hesitancy seven new vaccines have been successfully introduced in the last decade (e.g. Chickenpox, HPV, Rotavirus) and new ones are close to introduction (e.g. Herpes Zoster, Gonorrhea, Norovirus, RSV). Are policy-maker changing the traditional reluctant attitude against new vaccines? Few factors have been underlined in the last decade: Vaccination cost-benefit analysis offer politicians a good argument to show they are working for the population health. Mathematical models are becoming frequently used tools to show the economic gain of vaccination. The consequences of fake news and antivaccine narrative are warning politicians for more respect for science. Newly emerging epidemic diseases are increasing population confidence for public health interventions. Those factors are influencing health communication and could become useful tools to complement policy-makers' strategies.